From Katoomba to Jenolan Caves : the Six Foot Track, 1884-1984 - Smith, Jim, 1948- (Katoomba : Second Back Row Press, 1984)
"A Megalong book'
"A Megalong book'.
Maps on lining papers.
Bibliography: p. [155]-166.
Keywords: Travelers -- New South Wales -- Blue Mountains; Hiking -- New South Wales -- Blue Mountains; Blue Mountains (N.S.W. : Mountains) -- Description and travel